PUSAT INFORMASI PARIWISATA KABUPATEN SUMBA TENGAH BERBASIS WEBSITE - Adelbertus Umbu Janga (Universitas Merdeka Malang, 2017)
Technological developments rapidly growth such as the internet, it is time information management manual was gradually replaced by the information management that is technology. For it is necessary such as the design of information system of tourism in a web-based Central Sumba Regency. As for the purpose of this research is to help Central Sumba Regency Government to attract tourists visit through. To make all the content of the information contained onthe web has the administration control panel to be able to do pengelolahan add, editand delete data on tourism. Software developed in the preparation of this final Task using HTML (Hypertext Markup Language) which is the basic language for web scripting and client side that allows the display of information in the form of text, grafiks, and also to connectbetween the display Page (Hyperlink). In addition it is also used to program PHP and MySQL to create information systems be accurate. The end resulct of this research is produced a web-based application program that can give you an idea of the information system of tourism Central Sumba Regency that can display information about the profile of tourism.